Iryna, Y., Irja, S., Kuulo, K., Shaxob, S., Yusufjon, G. & Kerry, O. (2016) Epitypification of Morchella steppicola (Morchellaceae, Pezizales), a morphologically, phylogenetically and biogeographically distinct member of the Esculenta Clade from central Eurasia. Phytotaxa 284 (1): 31–40. - Yatsiuk, Iryna; Saar, Irja; Kalamees, Kuulo; Sulaymonov, Shaxob; Gafforov, Yusufjon; O’donnell, Kerry (Phytotaxa, 2016)
N/A